An Empirical Analysis of Experts' Perceptions on Reforming Sri Lanka's Muslim Marriage and Divorce Act of 1951: Perspectives on Sharia and Modernity - Long, Ahmad Sunawari; Saujan, Iqbal; Nafees, Seeni Mohamed Mohamed; Razick, Ahamed Sarjoon; Jubba, Hasse (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
The Muslim Marriage and Divorce Act No. 13 of 1951 (MMDA) provides a distinct legal framework governing marriage, divorce, polygamy, guardianship, Quazi court procedures, and maintenance among Sri Lankan Muslims. Debates over its reform have generated significant internal polarization. Reformist groups advocate amendments that respond to contemporary social realities, particularly women's rights and procedural justice. In contrast, conservative groups argue that any reform must remain consistent with Islamic Sharia, religious norms, and established customary practices (ʿurf). This study examines expert perceptions of the most contested issues in the proposed MMDA reforms. Using a quantitative descriptive design, 300 self-administered questionnaires were distributed to legal and religious scholars, Quazi judges, Arabic college principals, academics, postgraduate students, and prominent Muslim community leaders. A total of 250 valid responses were analyzed using SPSS version 24. The findings indicate strong support for several reforms, including the introduction of clear eligibility criteria for Quazis, supported by 94.3% of respondents; strengthening women's maintenance rights by considering husbands' income, 84%; requiring women's consent in marriage contracts, 75%; and establishing separate Quazi court operations, 88%. Respondents also showed moderate support for setting a minimum marriage age, 53%, and regulating the conditions of polygamy. However, resistance remained toward women's autonomous partner selection, the appointment of female Quazis, the removal of the term "sect," and the expansion of the law to include all madhhabs. The study concludes that MMDA reform in Sri Lanka requires a balanced legal approach that reconciles Islamic legal authority, community identity, gender justice, and contemporary standards of procedural fairness.